Cultural tourism: a neglected dimension of tourism industry - Debes, Tacgey (Routledge Journals, Taylor & Francis Ltd, 2011)
The aim of this paper is to highlight the cultural aspects of a country as a Mediterranean island (North Cyprus) where tourism is the main economic sector. Cultural products are drawing significant attention as interest in experiencing and learning about different cultures has grown widespread among tourists today. The assumption is that if tourism policy makers are not clearly defining their cultural values, along with appropriate strategies to restore their authenticity, it is likely that most of the cultural uniqueness will be underutilized and eventually lost. A qualitative research strategy has been employed and an in-depth semi-structured set of interview questions were administered to the informants in numerous culturally involved institutions. The study revealed that, notwithstanding the rich cultural assets and abundance of heritage, North Cyprus has not been able to develop a clear strategy towards cultural and heritage planning for the purpose of tourists' consumption.
Keywords: cultural/heritage tourism; cultural commoditization; cultural institutions; authenticity; identity